2016
DOI: 10.1242/jcs.182741
|View full text |Cite
|
Sign up to set email alerts
|

The membrane attack complex, perforin and cholesterol-dependent cytolysin superfamily of pore-forming proteins

Abstract: The membrane attack complex and perforin proteins (MACPFs) and bacterial cholesterol-dependent cytolysins (CDCs) are two branches of a large and diverse superfamily of pore-forming proteins that function in immunity and pathogenesis. During pore formation, soluble monomers assemble into large transmembrane pores through conformational transitions that involve extrusion and refolding of two α-helical regions into transmembrane β-hairpins. These transitions entail a dramatic refolding of the protein structure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 77 publications
(134 reference statements)
1
58
0
Order By: Relevance
“…Tsl has been detected in the plasma membrane at the two ends of the early embryo (Martin et al, 1994;Mineo et al, 2015) and Tsl bears a MACPF motif (Ponting, 1999), which is found in proteins known to become inserted into lipid bilayers (Lukoyanova et al, 2016). One possibility is that Tsl may modulate the local membrane environment in which Torso resides, perhaps by organizing lipid microdomains and thereby driving the formation of complexes competent to signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsl has been detected in the plasma membrane at the two ends of the early embryo (Martin et al, 1994;Mineo et al, 2015) and Tsl bears a MACPF motif (Ponting, 1999), which is found in proteins known to become inserted into lipid bilayers (Lukoyanova et al, 2016). One possibility is that Tsl may modulate the local membrane environment in which Torso resides, perhaps by organizing lipid microdomains and thereby driving the formation of complexes competent to signal.…”
Section: Discussionmentioning
confidence: 99%
“…Tsl is expressed during oogenesis in two groups of follicle cells that lie adjacent to the poles of the developing oocyte (Stevens et al, 1990;Savant-Bhonsale and Montell, 1993;Martin et al, 1994). Tsl is a secreted protein that carries a membrane attack complex/perforin (MACPF) domain found in a number of proteins known to oligomerize to form membrane pores (Ponting, 1999;Lukoyanova et al, 2016). Tsl becomes localized to the anterior and posterior regions of the vitelline membrane (VM) (Stevens et al, 2003): the inner layer of the eggshell that surrounds the developing embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CDCs are released into the extracellular environment as water-soluble monomers (or dimers) and oligomerize upon binding to cholesterol-containing membranes into a pre-pore complex of 35 to 50 CDC subunits. This oligomerization is accompanied by dramatic conformational changes induced by a combination of protein-protein and protein-lipid interactions resulting in the conversion of α-helices into β-strands for the formation of a large transmembrane β-barrel pore (Hotze and Tweten, 2012; Lukoyanova et al, 2016). …”
Section: Common Features Of Toxins and Inactivation Mechanisms By Defmentioning
confidence: 99%
“…Examples of lipid-specific pore-formation include Plasmodium CelTOS that depends on phosphatidic acid for pore formation, and the cholesterol dependent cytolysins (Jimah et al ., 2016; Lukoyanova et al ., 2016). CelTOS (cell traversal protein for ookinetes and sporozoites) is a malaria parasite protein that disrupts host cell membranes by pore formation to enable the exit of parasites from invaded host cells during cell traversal (Kariu et al ., 2006; Jimah et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CelTOS (cell traversal protein for ookinetes and sporozoites) is a malaria parasite protein that disrupts host cell membranes by pore formation to enable the exit of parasites from invaded host cells during cell traversal (Kariu et al ., 2006; Jimah et al ., 2016). Cholesterol dependent cytolysins are a large class of pore-forming proteins, including virulence factors of gram positive bacteria such as pneumolysin and listeriolysin (Lukoyanova et al ., 2016). Identifying the specific lipids targeted informs the mechanism of membrane disruption that underlies biological function and role of proteins and biomolecules.…”
Section: Introductionmentioning
confidence: 99%